(3x+6)+(x+2)=4(x-1)+7

Simple and best practice solution for (3x+6)+(x+2)=4(x-1)+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+6)+(x+2)=4(x-1)+7 equation:


Simplifying
(3x + 6) + (x + 2) = 4(x + -1) + 7

Reorder the terms:
(6 + 3x) + (x + 2) = 4(x + -1) + 7

Remove parenthesis around (6 + 3x)
6 + 3x + (x + 2) = 4(x + -1) + 7

Reorder the terms:
6 + 3x + (2 + x) = 4(x + -1) + 7

Remove parenthesis around (2 + x)
6 + 3x + 2 + x = 4(x + -1) + 7

Reorder the terms:
6 + 2 + 3x + x = 4(x + -1) + 7

Combine like terms: 6 + 2 = 8
8 + 3x + x = 4(x + -1) + 7

Combine like terms: 3x + x = 4x
8 + 4x = 4(x + -1) + 7

Reorder the terms:
8 + 4x = 4(-1 + x) + 7
8 + 4x = (-1 * 4 + x * 4) + 7
8 + 4x = (-4 + 4x) + 7

Reorder the terms:
8 + 4x = -4 + 7 + 4x

Combine like terms: -4 + 7 = 3
8 + 4x = 3 + 4x

Add '-4x' to each side of the equation.
8 + 4x + -4x = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
8 + 0 = 3 + 4x + -4x
8 = 3 + 4x + -4x

Combine like terms: 4x + -4x = 0
8 = 3 + 0
8 = 3

Solving
8 = 3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 4x(-5)=16 | | 4y=2y-16 | | 4y=2y-8 | | -3(k+11)+6k=12(k-11) | | 4(3+3v)-3= | | x-4=-5x-4 | | 5(2x+3)=8(x-4) | | 5(x+5)=4(x-6)+x | | 1x-2x= | | 24+4x=6x+2 | | -4(x+1)+x=3(x+2)-10-6x | | 2(2u^2-4u)=12 | | 4(x+5)+7=4x+8 | | 5(8+6b)+5= | | 5x^2+11x-35=0 | | 7[x-4]=16 | | 5(x-3)+2x=7(x+3)-36 | | 3(2x-4)=-18 | | 6x-12=-18 | | 5-9x=107-30x | | 5k-(2k-18)= | | -8+12x=13+2x | | -16-5x=11-9x | | 4x+7-3x+22=35 | | -4=2(x-8)-4x | | 3y+28=19 | | 7y+5=40 | | 6y-3=39 | | 8y+19=-13 | | 4x+31=39 | | 2x-10=14+4x | | 3x-14=-26 |

Equations solver categories